"Putting things in context": Literal and discourse approaches to comprehension assessment - Paul, R. (Seminars in Speech and Language, 2000)
Research on receptive language development in typical children, especially as explicated in a classic paper by Robin Chapman, is reviewed. These findings raise three challenges for clinicians assessing comprehension in children with language disorders: (1) contrary to popular wisdom, comprehension does not always precede production in a simple step-by-step way; (2) comprehension is a private event; indicators of comprehension must be used to assess it, and these indicators can be misleading; and (3) children with subtle comprehension deficits may do well on standardized tests that are not sensitive to their difficulties with real-time discourse. Some strategies for addressing these challenges, as well as a framework for assessing comprehension, are offered.
11 citations (Crossref) [2023-10-31]
Keywords: *Child Language; *Cognition; *Language Tests; *Verbal Behavior; Child Language; Child; Preschool; Cognition; Comprehension assessment; Comprehension deficits; Comprehension stages; Discourse comprehension; Humans; Language Tests; Verbal Behavior; article; cognition; dept.cmd; human; language development; language test; preschool child; verbal behavior

TBI knowledge and pragmatic assessment among Connecticut school speech-language pathologists - McGrane, S.A.; Cascella, P.W. (Brain Injury, 2000)
School-based speech-language pathologists from Connecticut responded to a random survey which had a twofold purpose, (1) to replicate a previous conclusion that clinicians' specific experience with traumatic brain injury (TBI) influences their knowledge of this subject, and (2) to explore the topic of pragmatic assessment and whether it is also influenced by specific TBI experience. Results indicate that Connecticut school clinicians favourably regard both their own knowledge of TBI and the contemporary issue of pragmatic assessment. Connecticut clinicians also report a relatively low degree of prior TBI training and clinical experience. Clinicians' degree of TBI training and clinical experience did not appear directly related to their reported competence in TBI knowledge and pragmatic assessment.
10 citations (Crossref) [2023-10-31]
Keywords: *Brain Injuries/di [Diagnosis]; *Professional Competence; *Self-Assessment; *Speech-Language Pathology/ed [Education]; Adult; Connecticut; Female; Humans; Male; Middle Aged; Schools; Surveys and Questionnaires; Workforce; article; brain injury; competence; dept.cmd; education; experience; functional assessment; human; linguistics; normal human